Social media as content distribution channel for Belarusian mass media - Stsiapanau, Uladzimir A. (Journal of the Belarusian State University. Journalism, 2019)
The article presents the results of a content analysis of the materials of 15 Belarusian online media, which actively use accounts on VKontakte, Facebook and Twitter social media platforms for content distribution. The author argues that this function of social channels has the highest priority for mass media. The research summarizes the best practices of editorial offices, highlights the most typical approaches in content adaption for social media, includes the analysis of broadcasting formats, account stylistics, particular qualities of illustration approach. Much attention is given to internet memes – specific for social media form of illustration.